2018
DOI: 10.15740/has/au/13.2/123-127
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic profile and constraints faced by the members of milk producers co-operative societies in production and marketing of milk in Dharwad district of Karnataka- an analysis

Abstract: The present study attempted to study the socioeconomic profile of the sample dairy farmers and to document the problems faced by the members of milk producers cooperative societies in production and marketing of milk in Dharwad district. Multistage sampling procedure was followed for selection of 120 sample Dairy farmers. The data pertained to the agricultural year 2014-15. Tabular analysis and Garrett ranking technique were used to analyze the data. The socioeconomic profile of the sample dairy farmers with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
3
0
0
Order By: Relevance
“…The findings of the study revealed that the majority of respondents (54.16%) had a medium level of social participation, followed by a low level (34.16%) and a high level (11.66%) of social participation. Similar results were supported by studies conducted by Thaker et al (2020) [37] and Upretil and Bhardwaj, (2018) [10] . It was observed that most of them were members of milk co-operative societies to fulfil the essentials of dairy farming, including timely economic support.…”
Section: Social Participationsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings of the study revealed that the majority of respondents (54.16%) had a medium level of social participation, followed by a low level (34.16%) and a high level (11.66%) of social participation. Similar results were supported by studies conducted by Thaker et al (2020) [37] and Upretil and Bhardwaj, (2018) [10] . It was observed that most of them were members of milk co-operative societies to fulfil the essentials of dairy farming, including timely economic support.…”
Section: Social Participationsupporting
confidence: 90%
“…It was observed that, the middle age group is commonly engaged in women's dairy co-operative activities as they shouldered the family responsibilities very efficiently. Similar findings were also recorded by Gadad and Kunnal (2018) [10] , wherein they reported that the majority of the farmers were in the middle age group (49.17%), followed by the old age group (40%) and young age group (10.83%) respectively. These observations were also in harmony with the findings of Nikita et al (2018) [40] , Ravinder and Umadevi, (2020) [33] , Kochar and Kaur (2015) [20] .…”
Section: Socio-economic Profile Of Members Of Women Dairy Cooperative...supporting
confidence: 88%
See 1 more Smart Citation